1963
DOI: 10.1071/ch9630596
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus Compounds. I. 2-Chloroalkylphosphonic Acids as Phosphorylating Agents

Abstract: Alcohols and phenols are phosphorylated in high yield by reaction with various 2-chloroalkylphosphonic acids at 20-50�C in the presence of three or more molar equivalents of cyclohexylamine or triethylamine, the other products being the corresponding alk-1-ene and chloride ion. The reaction probably proceeds by attack of an ROH molecule on the phosphorus atom of a doubly-ionized phosphonate group. 2-Chlorodecyl-, 10-carboxy-2-chlorodecyl-, and 2-chloro-octylphosphonic acid decompose rapidly in neutral soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
47
0
1

Year Published

1969
1969
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 0 publications
1
47
0
1
Order By: Relevance
“…A number of groups have studied aspects of the breakdown of the acid (1, 4-6). Maynard and Swan (4) showed that the products are chloride ion, ethylene, and phosphate. The yield of ethylene was found to be quantitative (1,5), and according to Yang (6), the yield of phosphate is also quantitative.…”
mentioning
confidence: 99%
“…A number of groups have studied aspects of the breakdown of the acid (1, 4-6). Maynard and Swan (4) showed that the products are chloride ion, ethylene, and phosphate. The yield of ethylene was found to be quantitative (1,5), and according to Yang (6), the yield of phosphate is also quantitative.…”
mentioning
confidence: 99%
“…LG:, just as C-P scission occurs only in the dianion, but not in the monoanion, of a 2-haloalkylphosphonic acid (Maynard and Swan, 1963). Similarly diazotization of -0 -P(O)(Ph) -CHz -CH2 -NH; , but not of Ph2P(0) -CH2 -CH2 -NH;, gave C-P scission (Mastalerz and Richtarski, 1971).…”
Section: Results and Dlscussionmentioning
confidence: 99%
“…Presumably departure of Nz from -H 0 3 P -CH2 -CH-(-N ' 2) -COOH is accompanied by scission of the P-C bond rather than attack of 01 on C2, the usual reaction when 2-amino acids are diazotized. The reaction is thus like the diazotization of aminoethylphosphonic acid studied by Mastalerz and Richtarski (1971), and closely analogous to the Conant-Swan breakdown in base of 2-haloalkylphosphonic acids (see Maynard and Swan, 1963); it is one of the reactions analysed by Clark et al (1964) as a P-XYZ system in which Z accommodates electrons and it is similar to the mechanism of natural splitting of the C-P bond (La Nauze et al, 1977;Olsen et al, 1988) and to the release of phosphate when 1-aminoalkylphosphonic acids react with ninhydrin (Warren, 1966). When, however, 2 mol/mol HBr was added, no phosphate was released (and bromo acid rather than hydroxy acid was the main product).…”
Section: Results and Dlscussionmentioning
confidence: 99%
“…The chemical mechanism of ethylene production from CEPA suggested by Maynard and Swan (5) involves the nucleophilic attack on -the phosphonate dianion by a water molecule and the concerted elimination of chlorine, leading to direct formation of phosphate and chloride as shown in equation (I). Probably the OH-ion may also serve as an nucleophile in the reaction.…”
mentioning
confidence: 99%